PENGARUH KOMPENSASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. INTEK LAMPUNG - Miswan Gumanti; Yoeyong Rahsel (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to determine whether there is a significant effect of compensation, motivation, and work environment simultaneously and partially on employee performance at PT. Intek Lampung. The research method used is associative research, while the sampling uses Nonprobability Sampling with saturated sampling method involving 87 respondents in the production department. The data analysis method uses the average method, scale range, multiple linear regression, F and T statistical tests. The results of the study show that: Compensation, motivation, and work environment simultaneously have a significant effect on employee performance and partially compensation, motivation, and work environment. work environment has a significant effect on employee performance Keywords : Compensation, Motivation, Work Environment and Performance